Arquivo morto em fabulação: do encontro entre Seu Cosme e Estamira no “além do além” - Almeida, Laís Suelen Gonzaga (2023)
In a moment of necro-capitalism, in which many bodies, for not being worth anything, are worth more dead, from this place of death, loss and ruins, two swallows return, banging their beaks on our windows, inviting us to fable a life, a people, a search. From the encounter between researcher, swallows and the world, seeking ways out between resentment and numbness, a story of ordinary Brazilian people was created, people killed by capital, people who ended up in the archives of mental health services, even if one even became documentary. Through a bird-like writing, Estamira finds Seu Cosme, weaving a life that can and is done in an act of another, announcing the astonishment of the lukewarmness of this capital life and the symptom of these times: the killing. Opening the archives shelved in the rooms and the memory archives; opening the body to encounters; Opening the words, the scientist went “beyond the beyond”, a place where, according to Estamira, no scientist had ever arrived. A shaky, stuttering and delirious cartographic conceptual-methodological path was followed, in an intersection between Gilles Deleuze's typology and his concept of fabulation, Antônio Lancetti's clinic of deviation, the concept of necrobiopower proposed by Berenice Bento and other references that composed a history of the present, a vital memory, intending to make/provide science to question and resist the mechanisms of production, control and death of the bodies and subjectivities of black, poor, old people, who do not adhere to the time-space of entrepreneurship in yes.